Optical and electro-optic anisotropy of epitaxial PZT thin films - Tok, Alfred Iing Yoong (2015)
Strong optical and electro-optic (EO) anisotropy has been investigated in ferroelectric Pb(Zr0.48Ti0.52)O3 thin films epitaxially grown on Nb-SrTiO3 (001), (011), and (111) substrates using magnetron sputtering. The refractive index, electro-optic, and ferroelectric properties of the samples demonstrate the significant dependence on the growth orientation. The linear electro-optic coefficients of the (001), (011), and (111)-oriented PZT thin films were 270.8, 198.8, and 125.7 pm/V, respectively. Such remarkable anisotropic EO behaviors have been explained according to the structure correlation between the orientation dependent distribution, spontaneous polarization, epitaxial strain, and domain pattern.